EPIDEMIOLOGICAL STUDIES ON TUBERCULOSIS IN BUFFALO POPULATION IN VILLAGES AROUND FAISALABAD - M. Arshad; M. Ifrahim; M. Ashraf; S. U. Rehman; H. A. Khan (Journal of Animal and Plant Sciences, 2012)
Faisalabad is the third largest city of Pakistan with an approximate population of 2.6 million. Most of the raw milk supplied in the city for consumption of the people comes from peri-urban areas of the city. Bovine tuberculosis (TB) is one of the most important zoonotic diseases transmitted through milk. Disease has also economic importance due to decrease in milk production of affected animals. The present study was conducted to measure the prevalence and some associated factors of bovine TB in buffaloes in peri-urban areas of Faisalabad city. A total of 1052 buffaloes were selected through cluster random sampling considering every dairy herd as a cluster in the villages within 15 kilometer radius from Clock Tower of Faisalabad City from year 2005 to 2008. Number of animals selected during the years 2005, 2006, 2007 and 2008 were 263, 259,264 and 266 respectively. The epidemiological data were collected on factors like age, sex, physical condition, milk yield and housing of the animals on pre-designed data capture forms. All the animals were tested for TB through single intra-dermal comparative tuberculin test (SICTT). The prevalence of TB in buffaloes was recorded as 2.47 %. The temporal distribution over a period of years revealed that the disease is endemic in buffalo population in peri-urban areas of Faisalabad city with prevalence of 2.26 to 2.70 %. Age, physical condition, milk yield and housing of the animals were found associated with the disease through chi-square test while sex of the animal did not show any association with the disease. The animals of 5-8 years of age were at highest risk of disease with prevalence of 4.04 to 5.04 %. No animal up to one year age was found positive. The animals with poor physical conditions (5.05) had 2.8 times higher prevalence than the animals with good health conditions (1.80). When association between milk yield and the disease was investigated, the buffaloes with highest prevalence (6.57%) of disease had daily milk yield of 4-6 liters. No reactor belonged to the group having milk yield of 10-12 liters. The animals maintained under closed housing had significantly higher prevalence (3.57) than the animals kept under open housing conditions (1.35%). It is suggested that all the dairy animals in the peri-urban areas of Faisalabad city should be tested regularly for prevalence of bovine TB by Department of Animal Health/Public Health Department. The animals found positive should be removed from the dairy population through appropriate compensation to the dairy farmers for safety of the human health and reduce the milk losses caused by the disease. The raw milk should never be consumed by the people in any way.
Keywords: Bovine tuberculosis; Zoonotic diseases; Buffaloes; Peri-urban areas; Prevalence; Cluster random sampling; Single intra-dermal comparative tuberculin test (SICTT); Epidemiological data; Endemic disease